Endogenous Acute Phase Serum Amyloid A Lacks Pro-Inflammatory Activity, Contrasting the Two Recombinant Variants That Activate Human Neutrophils through Different Receptors - Christenson, Karin; Björkman, Lena; Ahlin, Sofie; Olsson, Maja; Sjöholm, Kajsa; Karlsson, Anna; Bylund, Johan (Frontiers in Immunology, 2013)
Most notable among the acute phase proteins is serum amyloid A (SAA), levels of which can increase 1000-fold during infections, aseptic inflammation, and/or trauma. Chronically elevated SAA levels are associated with a wide variety of pathological conditions, including obesity and rheumatic diseases. Using a recombinant hybrid of the two human SAA isoforms (SAA1 and 2) that does not exist in vivo, numerous in vitro studies have given rise to the notion that acute phase SAA is a pro-inflammatory molecule with cytokine-like properties. It is however unclear whether endogenous acute phase SAA per se mediates pro-inflammatory effects. We tested this in samples from patients with inflammatory arthritis and in a transgenic mouse model that expresses human SAA1. Endogenous human SAA did not drive production of pro-inflammatory IL-8/KC in either of these settings. Human neutrophils derived from arthritis patients displayed no signs of activation, despite being exposed to severely elevated SAA levels in circulation, and SAA-rich sera also failed to activate cells in vitro. In contrast, two recombinant SAA variants (the hybrid SAA and SAA1) both activated human neutrophils, inducing L-selectin shedding, production of reactive oxygen species, and production of IL-8. The hybrid SAA was approximately 100-fold more potent than recombinant SAA1. Recombinant hybrid SAA and SAA1 activated neutrophils through different receptors, with recombinant SAA1 being a ligand for formyl peptide receptor 2 (FPR2). We conclude that even though recombinant SAAs can be valuable tools for studying neutrophil activation, they do not reflect the nature of the endogenous protein.